A multi-criteria approach to affordable energy-efficient retrofit of primary school buildings - Moazzen, Nazanin; Ashrafian, Touraj; Yilmaz, Zerrin; Karaguler, Mustafa Erkan (Elsevier BV, 2020)
Abstract The majority of the buildings was built before the energy efficiency prospering in the construction sector. Hence, they are consuming an enormous energy amount that can be preserved considerably by applying some not even advanced retrofit measures. Schools' low budget is a problem that managers are encountered. Thus the high retrofit cost can prevent taking proper actions. However, considering the measures leading to higher energy efficiency with appropriate cost and payback period, together with taking the lifespan of buildings and the economic benefits during this extended period, would make the actions attractive. This research aims at defining a multi-parameter approach to distinguish energy efficient measures with proper cost, payback period and CO2 emission for primary school buildings’ retrofit. It is following the concept of cost-optimal building retrofit introduced by the EPBD-recast. To assess the proposed approach, two typical school buildings were considered as case studies, the model was created and validated by real consumptions, and then some measures were applied to the envelope, mechanical and lighting system. After driven cost-optimal measures, the comfort analyses were conducted and some of the measures were excluded due to worsening the comfort conditions. The results indicate that, in the suitable cost-optimal scenarios, the potential of primary energy savings and CO2 emission reductions are approximately 60%, and savings for global cost would amount to more than 42%, while the payback periods are less than seven years.
Keywords: School buildings; Occupant comfort; Payback period; Consumption; Performance; Multiobjective optimization; Energy-efficient retrofit; COST-OPTIMAL RENOVATION; Multistage; Validation; Cost-optimal